2018
DOI: 10.3390/met8100854
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Treatment Strategies for Additively-Manufactured Tools of X37CrMoV5-1

Abstract: For cost-intensive products like automobiles, clients often wish to personalize their product, what forces the industry to create a large diversity of combinable parts. Additionally, the life cycles of many components become shorter. For highly-stressable parts, which are commonly manufactured by forging, the short changeover cycles result in expensive products, as the costs of tools must be offset by the sale of only a few parts. To reduce the tool cost, new, flexible processes have to be established in tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…They are applied to build "ready-to-use" mechanical parts as well as tools (molds, dies, punches, etc.) [19,20]. Over the past few years, MAM methods have been used in the production of regular cellular structures [21][22][23][24] that demonstrate high energy absorption capacities with low relative densities [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…They are applied to build "ready-to-use" mechanical parts as well as tools (molds, dies, punches, etc.) [19,20]. Over the past few years, MAM methods have been used in the production of regular cellular structures [21][22][23][24] that demonstrate high energy absorption capacities with low relative densities [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…High hardness together with high yield strength are significant properties for wear reduction in order to extend the tool life. EBM provides higher hardness than conventionally manufactured PM material after austenitization and quenching, which can be a result of fine-grained martensitic and dendritic microstructure that results from the high cooling rates characteristic to EBM and laser-based PBF-AM, as stressed by Junker et al [ 30 ]. The discontinuous carbide network was also considered to be the reason for the relatively high compression strength.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, residual stress is any self-equilibrated stress system developed in a component in the absence of any externally applied load; indeed, as for any laser-based process [9], in DED, the formation of the residual stress is ascribed to rapid heating and cooling, due to focused energy. It has been already shown that untreated residual stress may induce fracture under loading and reduce the fatigue life and the mechanical properties of the repaired or coated part [10,11]; moreover, although proper heat treating can be performed to release the stresses depending on the metal alloy [12,13], deformations arising during the process may result in a mismatch with respect to the intended geometry and even compromise the product integrity [7,10] or the repair quality in general [3].…”
Section: Introductionmentioning
confidence: 99%